A Synthesis of a Dust Suppressant Using the Cellulose Extracted from Maize Straw. (16th December 2019) - Wang, Hongkun; Nie, Wen; Zhang, Haihan; Jin, Hu; Bao, Qiu; Yan, Jiayi; Liu, Qiang
Abstract: In this paper, a cellulose‐based dust suppressant is synthesized using common maize straw as the raw material. In order to obtain high‐quality cellulose, a chemical, acid‐based treatment is employed for the extraction of cellulose and the removal of hemicellulose and lignin. By using polyvinyl alcohol (PVC) as a monomer, potassium persulfate (K2 S2 O4 ) as an initiator, aluminum hydroxide (Al(OH)3 ) as a crosslinker, and glycerol (C3 H8 O3 ) as a plasticizer (mass ratios of 28.5%, 1.0%, 0.5%, and 19.0%, respectively), the polyvinyl alcohol grafted cellulose dust suppressant is fabricated in a water bath of 70 ˚C after 5 h. The characteristics of the dust suppressant are measured using a Fourier transform infrared spectrometry, scanning electron microscope, thermogravimetric analyzer, universal testing machine, and wind tunnel simulation platform. At a concentration of 5%, the dust suppressant demonstrates some excellent functionality, such as economic rationality, film‐forming capability, compression resistance, temperature adaptability, and wind erosion resistance. As the raw material is easy to obtain and pollution‐free, this new dust suppressant has promising market prospects. Abstract : The characteristics of the dust suppressant are measured using a Fourier transform infrared spectrometry, scanning electron microscope, thermogravimetric analyzer, universal testing machine, and wind tunnel simulation platform.